«Կենսական տարածքի» ընկալումները Միություն և առաջադիմություն կոմիտեի աշխարհայացքում և Հայոց ցեղասպանությունը - Գալուստյան, Ռեգինա Ա. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Հոդվածում փորձ է արվում ռատցելյան կենսական տարածքի տեսությունը տեղայնացնել Օսմանյան կայսրության գոյության վերջին քսանամյակի և իշխող Միություն և առաջադիմություն կոմիտեի (Ittihat ve Terakki, իթթիհաթականներ) քաղաքականության վրա: Համադրելով Ռատցելիուսմունքը 1908 թ. հեղաշրջուﬕ ց հետո, հատկապես Առաջին համաշխարհային պատերազմի ընթացքում իթթիհաթականների գաղափարական քարոզչության և երկրի տարածքը թրքացնելուն ուղղված գործնական քայլերի հետ` կարող ենք առաջ քաշել այն դրույթը, որ կոմիտեի քաղաքական տեսլականն ավելին էր, քան զուտ թուրքական ազգային պետություն ստեղծելը: Հոդվածում խնդիր է դրվել ուսումնասիրել կոմիտեի անդամների շրջանում Փոքր Ասիա թերակղզին և Հայկական լեռնաշխարհի արևմտյան հատվածը թուրքական կենսական տարածք ընկալելու գաղափարի ձևավորումը, զարգացումը, որի իրականացման գործնական քայլերը հանգեցրին բնիկ քրիստոնյա ժողովուրդների պետականորեն ծրագրված ոչնչացմանը: Friedrich Ratzel (1844-1904), a prominent thinker of political geography, put forward an idea of vital space (Lebensraum) by an analogy between a plant and a state. Developing this idea in the 1890s Ratzel defined the vital space as a precondition for a given state to provide proper living conditions for its population, without which the existence, development and further expansion of the state would be impossible. Although Ratzel’s theory was predominantly attributed to the Nazi regime and German quest for land in the East, the theory of Lebensraum could be localized on the Ottoman Empire and the policy of the Committee of Union and Progress (CUP). Juxtaposing the teachings of Ratzel with the ideological propaganda of the CUP as a ruling party from 1908-1918 and the practical steps taken towards the Turkification of the country, the article argues that the Committee’s political vision was more than just a creation of a Turkish nation-state. The formation and development of the perception of the Asia Minor peninsula and the western part of the Armenian Highlands as a Turkish vital space and the practical steps taken towards the maintenance of this land led to the deliberate destruction of the native Christian populations. The article will present the theoretical framework of Lebensraum, the development of the idea of “homeland” among the Turkish intellectual elite, the geopolitical and historical context in which “Anatolia” was chosen as a Turkish vital space. Interwoven with Herbert Spencer’s doctrine of social Darwinism, and its main concepts “struggle for survival” and the “survival of the fittest,” Ratzel’s Lebensraum became more comprehensible to political circles, including high-ranking offi cials of the Committee of Union and Progress. The paper discusses the preconditions for the selection of an area, methods of its conquest and maintenance. While the physical cleansing of the vital space from the “opponent” or “alien” population is one of the methods for maintenance of Lebensraum. Taking the Armenian Genocide as a clear example of this method, the article discusses only the economic and cultural inner expansions. The article concludes that the Armenian Genocide was a set of state-planned deliberate measures by the Ottoman government aimed at the physical destruction and full eradication of the Armenians from the Turkish living space and the social and cultural system of the country. Фридрих Ратцель (1844-1904), выдающийся мыслитель политической географии, выдвинул идею жизненного пространства (Lebensraum) по аналогии между растением и государством. Развивая эту идею в 1890-х годах, Ратцель определил жизненное пространство как необходимое условие для обеспечивания надлежащих условий жизни населения, без которого существование, развитие и дальнейшее расширение государства были бы невозможным. Хотя теория Ратцеля преимущественно приписывалась нацистскому режиму и немецким поискам земли на Востоке, теория “лебенсраума” может быть применена и к Османской империи, и политике Комитета “Единение и прогресс.” Сопоставляя учение Ратцеля с идеологической пропагандой Комитета как правящей партии в 1908-1918 годах и практическими шагами, предпринятыми в направлении тюркизации страны, в статье утверждается, что политическое видение Комитета выходит за пределы создания турецкого национального государства. Формирование и развитие восприятия полуострова Малой Азии и западной части Армянского нагорья как турецкого жизненного пространства и практические шаги, предпринятые для сохранения этой земли, привели к преднамеренному уничтожению коренного христианского населения. В данной работе представлены теоретические основы “лебенсраума,” развитие идеи “родины” среди турецкой интеллектуальной элиты, геополитический и исторический контекст, в котором “Анатолия” была выбрана в качестве турецкого жизненного пространства. Переплетаясь с учением Герберта Спенсера, социал-дарвинизмом и его основными понятиями “борьба за выживание” и “выживание наиболее приспособленных,” жизненное пространство Ратцеля стало понятным и приемлемым политическим кругам, включая высокопоставленных чиновников Комитета. В статье рассматриваются предпосылки выбора той или иной территории, методы ее завоевания и сохранения. В то время как физическое очищение жизненного пространства от “противника” или “чужого” населения является одним из методов освоения жизненного пространства, данная статья, принимая Геноцид армян в качестве наглядного примера этого метода, рассматривает только экономические и культурные внутренние экспансии. В статье делается вывод о том, что Геноцид армян представлял собой комплекс спланированных мер османского правительства, направленных на физическое уничтожение и полное искоренение армян из турецкого жизненного пространства и социально-культурной системы страны.
Keywords: Հայոց ցեղասպանություն; Հայոց պատմություն